2014
DOI: 10.1002/mawe.201400194
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural characterization and kinetics of diffusion bonded AZ31/Al by hot press cladding

Abstract: In the present investigation, magnesium alloy AZ31 sheet was covered by a commercial pure aluminium sheet by cladding using hot pressing. The influence of the applied pressure, temperature and holding time on the bond characteristics was studied. Microstructure examination of bonded specimens was experimentally investigated by optical microscope, SEM and EDX. The experimental investigation has revealed a good bond quality due to the effective mutual diffusion of Mg and Al. The phase analysis resulted in the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…From these results, it can be understood that the addition of short carbon fibers has an important contribution to make in improving the mechanical properties of AZ91, where the short carbon fibers are able to resist the load transfer applied during tensile testing through interfacial shear stress and thus exert a strengthening effect on AZ91 composites [ 39 ]. Obviously, this strengthening effect is greatly influenced by the distribution properties and the formation of good bonding strength between short carbon fibers as reinforcing material and AZ91 as the matrix [ 40 , 41 ]. In previous work, it was reported that carbon fibers can help the solidification of a magnesium alloy matrix by acting as heterogeneous nucleation sites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From these results, it can be understood that the addition of short carbon fibers has an important contribution to make in improving the mechanical properties of AZ91, where the short carbon fibers are able to resist the load transfer applied during tensile testing through interfacial shear stress and thus exert a strengthening effect on AZ91 composites [ 39 ]. Obviously, this strengthening effect is greatly influenced by the distribution properties and the formation of good bonding strength between short carbon fibers as reinforcing material and AZ91 as the matrix [ 40 , 41 ]. In previous work, it was reported that carbon fibers can help the solidification of a magnesium alloy matrix by acting as heterogeneous nucleation sites.…”
Section: Resultsmentioning
confidence: 99%
“…Materials 2023, 16, x FOR PEER REVIEW 7 of 18 the formation of good bonding strength between short carbon fibers as reinforcing material and AZ91 as the matrix [40,41]. In previous work, it was reported that carbon fibers can help the solidification of a magnesium alloy matrix by acting as heterogeneous nucleation sites.…”
Section: Tensile Testing Resultsmentioning
confidence: 99%
“…This is mainly due to the incorporation of short carbon fibers into the AE42 alloy, which causes the AE42 alloy—which acts as the matrix—to become brittle, resulting in a sharp increase in its ultimate tensile strength compared to the unreinforced AE42. The distribution and well-bonded nature of the short carbon fibers in the matrix were found to have a positive influence on the mechanical properties of the unreinforced AE42 [ 5 , 6 ]. Previous research has shown that carbon fibers can act as heterogeneous nucleation sites during the solidification of the magnesium alloy matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Reflecting on recent trends, the utilization of magnesium alloys has been used in automotive components [ 3 ], and it has even been reported that several types of magnesium alloys have begun to be used in the manufacturing industry for applications in electric vehicle chassis [ 4 ] and body structures [ 5 ]; this has attracted the attention of scientists worldwide to develop magnesium-based alloys and their composites for many applications. The choice of magnesium as a potential candidate for engineering applications is due to its good castability and machinability, high specific strength, and, more uniquely, well-controlled weldability [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%